2014
DOI: 10.1097/cad.0000000000000127
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effect of traditional Chinese herbal medicines against lung cancer

Abstract: Traditional Chinese herbal medicine (TCHM) is used widely alone or in combination with chemotherapy to treat lung cancer in China. Meta-analysis of clinical trials of TCHM against lung cancer suggested the potential, but not confirmed therapeutic effect. To gain detailed insight into the antilung cancer effects of TCHM, we searched for preclinical studies of TCHM against lung cancer published from 1995 to 2012 and systematically analyzed published articles focusing on the antitumor effect of individual TCHM in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 40 publications
(35 reference statements)
2
20
0
Order By: Relevance
“…These observations have been summarized also by analyzing the IC 50 values shown in Table 3, where both TIIA and CRY present higher IC 50 values on human colon adenocarcinoma cells Caco-2 than on LN-229 and U-87 MG glioblastoma cancer cell lines. Our results are in accordance with related studies that have indicated a role of tanshinones in the inhibition of cancer growth by induction of apoptosis [49,50]. Thus, it was reasonable to speculate if tanshinones would play an important role in the inhibition of glioblastoma cell lines.…”
Section: Discussionsupporting
confidence: 93%
“…These observations have been summarized also by analyzing the IC 50 values shown in Table 3, where both TIIA and CRY present higher IC 50 values on human colon adenocarcinoma cells Caco-2 than on LN-229 and U-87 MG glioblastoma cancer cell lines. Our results are in accordance with related studies that have indicated a role of tanshinones in the inhibition of cancer growth by induction of apoptosis [49,50]. Thus, it was reasonable to speculate if tanshinones would play an important role in the inhibition of glioblastoma cell lines.…”
Section: Discussionsupporting
confidence: 93%
“…Based on our previous report, decursin has also similar functions, such as induction of selective ER stress via ROS generation and TRAIL sensitivity in lung cancer cells (18). Recent report indicated that Tanshinone IIA induces considerable amount of ROS formation in A549, but not H596 cells, which lack the NAD(P)H:quinone oxidoreductase (NQO1) (48). Consistently, we also detected ER stress response signals in Tanshinone IIA-treated A549 cells, but not in H596 (data not shown), indicating that ER stress induction by Tanshinone IIA may be mediated by ROS generation.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have been reported on the effects of plant extracts inhibiting tumor growth, metastasis, and angiogenesis [18]. This study was aimed to determine whether CG could induce cytotoxicity, examined in A549 and NCI-H1299 cells following treatment with various concentrations (up to 15 μg/ml for 24 and 48 h) of CG.…”
Section: Resultsmentioning
confidence: 99%